Experimental limit on an exotic parity-odd spin- and velocity-dependent interaction using an optically polarized vapor - Young Jin Kim (Nature Portfolio, 2019)
Symmetry breaking is an important process in fundamental understanding of matter and dark matter. Here the authors discuss an experimental bound on an exotic parity odd spin- and velocity-dependent interaction between electron and nucleon by using a sensitive spin-exchange relaxation-free atomic magnetometer.